2020
DOI: 10.1002/saj2.20004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sample preparation methods for characterizing the geochemistry of soils and sediments by portable X‐ray fluorescence

Abstract: We examined the impact of three different sample preparation methods on bulk soil geochemistry data obtained from a hand‐held, portable X‐ray fluorescence (pXRF) spectrometer. We generated data from a soil core recovered from the surface, downward into unaltered loess, and into a buried soil at a site in eastern Iowa. Samples were scanned (i) directly from field‐moist soil cores; (ii) after drying, grinding, and being loosely massed in plastic cups; and (iii) as pressed‐powder pellets. Data derived using these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Due to its complex formation, loess represents a geological and lithological mixture of its source areas. The different mineralogical components of loess deposits are prone to a multitude of methodological issues and sensible to, e.g., instrumentation or pretreatment of samples (Goff et al, 2020). Differences between different geochemical analysis techniques, such as inductively coupled plasma mass spectrometry (ICP-MS) and x-ray fluorescence analyses (XRF) can account to up to 10% of the measured contents (Miyazaki et al, 2016).…”
Section: Sampling and Laboratory Analyses Methodological Background Omentioning
confidence: 99%
“…Due to its complex formation, loess represents a geological and lithological mixture of its source areas. The different mineralogical components of loess deposits are prone to a multitude of methodological issues and sensible to, e.g., instrumentation or pretreatment of samples (Goff et al, 2020). Differences between different geochemical analysis techniques, such as inductively coupled plasma mass spectrometry (ICP-MS) and x-ray fluorescence analyses (XRF) can account to up to 10% of the measured contents (Miyazaki et al, 2016).…”
Section: Sampling and Laboratory Analyses Methodological Background Omentioning
confidence: 99%
“…Removing moisture and amending the calibrations accounts for spectral interference in these situations (Goff et al . 2020; Ravansari et al . 2020).…”
Section: Resultsmentioning
confidence: 99%
“…2017; Luo and Bathurst 2017; Goff et al . 2020). These results showed that whilst homogenizing soil is required to increase the concentrations detected, there is no artificial impact on the relative distributions of all elements of interest.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations